The Green Prescription and New Zealand Older Adults: Motives, Benefits and Barriers - Patel, Asmita (Auckland University of Technology, 2010)
Despite empirical evidence for the health-related benefits of physical activity, a large proportion of older adults are insufficiently active. In New Zealand, the Green Prescription is the nationwide physical activity scripting programme. The Green Prescription has been found to be effective in increasing physical activity in previously low-active and sedentary adults. However, more information is required about the efficacy of Green Prescription use with older adults. The present research examined participants' views and experiences of physical activity counseling via the conventional Green Prescription and a modified pedometer-based Green Prescription. Both versions of the Green Prescription were effective in increasing and maintaining physical activity over a 12-month period. Demographic factors were found to significantly influence perceived barriers and motives for physical activity regardless of type of Green Prescription administered.
Keywords: Older adults; Motives; Physical activity; Green prescription; Barriers